REFLECTION OF LOW-FREQUENCY WAVES PROPAGATING IN A COMPRESSIBLE LIQUID AT NORMAL INCIDENCE ON A POROUS MEDIUM - Bordakov G.A.; Mikolaevskii E.Yu.; Sekerzh-Zenkovich S.Ya. (My University, 2000)
This study is concerned with the analytical solution of a problem, pertaining to marine seismic prospecting, in low-frequency wavelets propagating in a compressible liquid (an upper half-space) and incident on a porous fluid-saturated material which is either a lower half-space or a thin layer overlying an elastic half-space. The reflected signal is shown to involve slowly decaying (in space and time) "tails" in the former case, whereas in the latter case the effect of the porous material results in a time shift in the reflected signal compared to reflections from an elastic half-space.